2016
DOI: 10.1007/s10549-016-3869-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ataxia-telangiectasia-mutated protein expression correlates with poor prognosis but benefits from anthracycline-containing adjuvant chemotherapy in breast cancer

Abstract: We investigated the correlation of ataxia-telangiectasia-mutated (ATM) protein expression with clinicopathological features and prognosis in patients with breast cancer. ATM expression was determined by immunohistochemistry in 420 surgically resected breast tumors. ATM loss was observed in 126/407 evaluable cases (31.0 %), and was significantly associated with larger tumor size, lymph node metastasis, higher tumor grade, and ER- and/or PR-negative status. ATM loss was also associated with significantly lower d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[19]. Similarly, quantitative IHC of ATM in breast cancer identified a smaller subgroup of ATM-deficient patients [26] than does standard histopathology [27], however in both of these studies ATM-loss was associated with poor DFS.…”
Section: Discussionmentioning
confidence: 99%
“…[19]. Similarly, quantitative IHC of ATM in breast cancer identified a smaller subgroup of ATM-deficient patients [26] than does standard histopathology [27], however in both of these studies ATM-loss was associated with poor DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed with formalin-fixed, paraffin-embedded tissue using Benchmark automatic immunostaining device (Ventana, Arizona, USA) as previously described. 12 The primary antibodies were diluted as follows: oestrogen receptor (ER) (1D5; Novocastra Laboratories, Newcastle, UK), 1:100; progesterone receptors (PR) (PgR636; DAKO, Hamburg, Germany), 1:200; human epidermal growth factor receptor 2 (HER2) (Ventana, Arizona, USA), 1:1; PD-1 (Cell Marque, California, USA), 1:20; PD-L1 (B7-H1) (Cell Signaling, Massachusetts, USA), 1:100; PD-L2 (B7-DC) (Sigma-Aldrich, Missouri, USA), 1:500; IDO (Millipore-Sigma, Massachusetts, USA), 1:30; TIM-3 (Abbexa Ltd, Cambridge, UK), 1:550; OX40 (Novus Biologicals, Colorado, USA), 1:125; OX40L (Millipore-Sigma, Massachusetts, USA), 1:30; B7-H2 (Novus Biologicals, Colorado, USA), 1:300; B7-H3 (Cell Signaling, Massachusetts, USA), 1:50; B7-H4 (Cell Signaling, Massachusetts, USA), 1:50. Nuclear expression of tumour cells was interpreted as positive for ER and PR, while membrane staining of tumour cells was considered positive for HER2.…”
Section: Immunohistochemical Analysis Of Immune Markersmentioning
confidence: 99%
“…Previously, it was reported that the loss of ATM and normal TP53 expression is associated with poor prognosis in PC patients [ 31 ]. Likewise, ATM expression can be used as a prognostic marker in breast, gastric, and gall bladder cancers [ 20 , 32 , 33 ]. Although we did not obtain any evidence that ATM loss has an impact on PC patient prognosis, we are the first to report that low phospho-ATM expression is significantly important for OS and DFS in PC patients.…”
Section: Discussionmentioning
confidence: 99%